Consciência, Liberdade e Moral em Descartes - Paula, Everton Lira Marcondes de (2013)
The objective of this dissertation is to analyze the question Consciousness, Freedom and Morality in Descartes . The Cartesian philosophy provides a new view of consciousness, freedom and morality which are the essence of Descartes philosophy. Each one of these three factors are connected to each other in the way a clock gear must be in harmony with its neighbours to function properly. In the unfolding of his philosophy, Descartes shows the role of each one of these factors gradually and continuously. Everything originates in cogito ergo sum and from this famous sentence is developed a new knowledge. The faculty of thinking leads to the knowledge of our own consciousness. It allows the man to be capable of distinguishing true from false. Armed with this capability the man has now the power of choice, free will, which connects directly with morality.